2021
DOI: 10.5296/ijhrs.v11i3.18856
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors and Job Performance: The Mediating Roles of Employee Engagement

Abstract: This research examines the relationship between motivational factors, job performance, employee engagement and the impact of motivational factors on job performance function of employee engagement as a mediator in the government sector in the Sultanate of Oman. A quantitative study methodology was used, and six hypotheses were evaluated using 111 representative government employees from the Ministry of Education. This study is a pilot test. This study uses quota sampling, and Statistical Package for the Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Drawing on this finding, some results (e.g., Yu et al, 2020;Almawali et al, 2021), in JD-R literature using a cross-temporal research design, should be explained with caution.…”
Section: Discussionmentioning
confidence: 92%
“…Drawing on this finding, some results (e.g., Yu et al, 2020;Almawali et al, 2021), in JD-R literature using a cross-temporal research design, should be explained with caution.…”
Section: Discussionmentioning
confidence: 92%
“…It is proven that there a relationship between motivation and job performance among public sector employees, which the employee has a good motivation, the job performance can be increase. The studies such as (Syamsir, 2020;Stefurak et al, 2020;Uka & Prendi, 2021;Schwarz et al, 2020;Maryani et al, 2021;Anisya et al, 2021;Almawali et al, 2021;Amha & Brhane, 2020;Mariana, 2020;Wahyudi et al, 2023;Sunarsi et al, 2021;Alam et al, 2021;Widarko & Anwarodin, 2022;Kurniasih et al, 2022;Adetola et al, 2022;Dharmanegara et al, 2021;Tenrisanna et al, 2021;Sudha et al, 2023;Kuswati, 2020;Riwukore et al, 2022;Riwukore et al, 2021: Ratnawati et al, 2020Niati et al, 2021;Suriyanti, 2020;Rivaldo, 2021;Sumaiti, 2021;Virgiawan et al, 2021;Sukhumvito et al, 2020;Noor et al, 2020;Al-Jedaia & Mehrez, 2020;Guo et al, 2021;Syaharudin et al, 2022;Andika & Darmanto, 2020). These findings may have consequences for the government, which has to recognise the value of employee motivation to boost output and enhance performance.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…However, study by Jufrizen et al (2021) found motivation is not a moderator in relationship between organizational culture and job performance. Most of studies shown that there a significantly positive relationship between motivation and job performance such as studies by (Syamsir, 2020;Schwarz et al, 2020;Stefurak et al, 2020;Uka & Prendi, 2021;Maryani et al, 2021;Anisya et al, 2021;Almawali et al, 2021;Amha & Brhane., 2020;Mariana, 2020;Wahyudi et al, 2023;Sunarsi et al, 2021;Alam et al, 2021;Widarko & Anwarodin, 2022;Kurniasih et al, 2022;Adetola et al, 2022;Dharmanegara et al, 2021;Tenrisanna et al, 2021;Sudha et al, 2023;Kuswati, 2020;Riwukore et al, 2022;Riwukore et al, 2021;Ratnawati et al, 2020: Niati et al, 2021Suriyanti, 2020;Rivaldo, 2021;Sumaiti, 2021;Virgiawan et al, 2021;Sukhumvito et al, 2020;Noor et al, 2020;Al-Jedaia & Mehrez, 2020;Guo et al, 2021;Syaharudin et al, 2022;Andika & Darmanto, 2020). Some studies such as Apex-Apeh et al (2020); Andika and Darmanto (2020); Sultana et al (2021); Noviani (2021) found that intrinsic motivation has significant influence on job performance, however extrinsic motivation does not have significant with job performance (Apex-Apeh et al, 2020).…”
Section: Research Objective 2 -Relationship Motivation and Job Perfor...mentioning
confidence: 99%
“…In other words, the purpose is to provide workers with a well-rounded perspective of how others see their contributions in areas like cooperation, communication, leadership, and interpersonal interaction. Coworkers may use the assessment to gauge how well an employee is doing in terms of helping the company accomplish its objectives and having a good impact on the customers they serve according to Almawali et al (2021). With the assessment approach, employees get immediate feedback, and extraneous data is removed, preventing information overload.…”
Section: B Management By Objectives and Its Impact On Employee Produc...mentioning
confidence: 99%
“…A company's workers are critical to its future development and success. In many ways, they represent a company's image (Almawali et al, 2021). Employees are the most critical resource a business may utilize to complete its tasks since they are the most valuable, expensive, and inconsistent.…”
Section: Introductionmentioning
confidence: 99%